QUALITY MANAGEMENT OF HEALTH SERVICES ON PATIENT SATISFACTION AT MONTELLA PRIVATE HOSPITAL WEST ACEH DISTRICT - Mulya Wulandari; Susy Sriwahyuni; Dahlan Gunawan (PT. Radja Intercontinental Publishing, 2023)
The world of health is one of the most important factors in life. Over time, it is only natural for the world of health to provide fast and appropriate services in order to create a comfortable, conducive and motivated work environment. Hospital health services are one type of public service that is often accessed by the public. At any time the community will always demand quality services, even though these demands are often not as expected, because services still display a convoluted, slow, expensive and tiring nature because the community is still positioned as the party serving not being served. The purpose of this study was to determine the effect of the quality of health services on patient satisfaction at the Montella Private Hospital, West Aceh District. The method used in this study is simple linear regression where this method is used to determine the linear relationship between the independent variable (X) and the dependent variable (Y). In addition, the simple linear regression method aims to determine the direction of the relationship between the independent variable and the dependent variable. whether positive or negative and to predict the value of the dependent variable if the value of the independent variable increases or decreases. The data used is data from the answers to the questionnaire using a Likert scale. Based on the results of the study, it can be concluded that testing from previous observational data indicates that the magnitude of the influence of Health Service Quality on Patient Satisfaction at Montella Private Hospital as measured through the questionnaire question indicators distributed to respondents in the Very high and good category because it is influenced by 97.50% ( R Square value) so that it is proven that the variable Quality of Health Services has a large positive and significant effect on patient satisfaction at Montella Private Hospital, while the remaining percentage value of 2.50% affects variables not examined in this study's observations.